PERILAKU PROFESIONAL TENAGA KESEHATAN DAERAH PESISIR PADA PELAYANAN KESEHATAN PRIMER WILAYAH PUSKESMAS TANAH MERAH KABUPATEN INDRAGIRI HILIR TAHUN 2014 - Anggraini, Tiara; Afandi, Dedi; Chandra, Fifia (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
As a developing country, Indonesia continues to strive for the welfare of society. One of the efforts is to improve the proper health services, especially in coastal areas. The success of health services should be supported by the medical workers who have the role of professional conduct . The aim of this research is to discover the professional behavior of health-care workers of Tanah Merah community health care (Puskesmas), Indragiri Hilir Regency, that was reflected by the six elements of professionalism. The design of this research uses exploration method with qualitative approaches on five health-care workers of Puskesmas Tanah Merah, Indragiri Hilir Regency, who were selected by using snowball sampling method. Data collection was done by interview and recorded with an audio recorder. The result of this research showed that all the informants possess altruism, accountability, excellence, duty, honor and integrity, and respect for other.Key word : professional behavior, health-care workers.